The Spectrophotometric Determination of Samarium (III) With (l-2(2-Benzoinidazoly-AZO)-2-Hydroxy-3Naphthoic Acid - Hammodi, A.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Samarium(III) ions react with (l-2(2-benzoinidazolyl-azo)-2-hydroxy-3-naphthoic acid in basic medium (pH = 8.0) forms a red-orange complex at A.max (550nm). The complex was found to be stable for at least 48 hrs. at the given pH. The apparent molar absorptivity is 7776.77  L.mol-1.Cm-1 and a linear calibration curve is obtained in the range (0.639x  10-5M - 6.350x 10 -5M). The stoichiometry of complex was confirmed by using mole ratio method which indicated that ratio of reagent to metal is 3:1. The effects of the presence of different cations and anions as interferences in the determination of samarium(III) under the given conditions were investigated